Ivermection-loaded solid lipid nanoparticles: preparation, characterisation, stability and transdermal behaviour. (17th February 2018) - Guo, Dawei; Dou, Dandan; Li, Xinyu; Zhang, Qian; Bhutto, Zohaib Ahmed; Wang, Liping
Abstract: To avoid potential systematical toxicity, solid lipid nanoparticles (SLNs) were prepared as a vehicle for transdermal delivery of ivermectin (IVM) using hot homogenisation followed by ultrasonic method. The as-prepared SLNs were approximately spherical shape with good stability. IVM was encapsulated in amorphous form within SLNs and displayed prolonged release from SLNs without burst release due to high encapsulation efficiency (EE). The cumulative permeation of IVM across excised rat skin from SLNs was significantly increased compared to the ivermection suspension. These results indicated that the proposed SLNs can be considered as an efficient carrier for dermal delivery of IVM to effectively treat scabies.